Hållbar utveckling i gymnasieskolan - En intervjustudie med lärare om hur de arbetar med ämnet idag, och hur de önskar arbeta framöver - Carlestam,Jennifer (2018)
There are many measures that need to be taken in order to ensure a development that is sustainable. One of them is to educate for a sustainable development and increase the scientific literacy among students. This can create the requisites that are needed in order for students to become active citizens, who make informed decisions that promote a sustainable development in their everyday life. According to steering documents for the upper secondary school in Sweden, sustainable development needs to be integrated in the education. The aim of this study was to investigate how teachers in the upper secondary school interpret the concept of sustainable development, how they integrate it in their content teaching today, and how they want to do it in the future. Further, the study explored what educational material could support their work. In this study, semi-structured qualitative interviews with seven upper secondary school teachers in the subjects of natural and social science were carried out. This study shows that the interviewed teachers interpret sustainable development as a development where economic, ecologic and social sustainability depend on each other. Which of these dimensions that were given the biggest focus in the education were reflected by the teachers’ subjects. However, all teachers argued that all three dimensions were represented in their teaching. In the future, the teachers want to carry out more trans disciplinary collaborations, and integrate more practical elements in their teaching. Furthermore, it seems to be important that the complexity of issues related to sustainable development is shown, and that students are given a holistic understanding. The teachers requested an educational material that is flexible and easy to engage in their education, with clear linkage to the steering documents.
Keywords: hållbar utveckling; gymnasieskolan; utbildning för hållbar utveckling; naturvetenskaplig allmänbildning; sustainable development; upper secondary school; education for sustainable development; scientific literacy